Pengarauh Burn Out dan Beban Kerja Terhadap Motivasi Kerja Serta Dampaknya Terhadap Kinerja Karyawan PT. Bawang Mas Pamekasan - Febrian Dimas J. Wibowo; Siti Mujanah; Achmad Yanu Alif Fianto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Burnout occurs due to high work pressure and high demands on the results of work carried out by employees, the work environment can also influence an employee's burnout, this decline in employee quality will have fatal consequences for the company, if this is not paid attention to by the company it will be detrimental company. These employees carry an increasingly heavy workload due to the imbalance between demands and the employee's abilities, employees who experience stress will always be filled with feelings of anxiety, tension, easily feel awkward and frustrated as well as psychosomatic complaints. The sample from this research was all 73 employees of PT. Bawang Mas in Pamekasan Regency using a saturated sampling technique. According to Arikunto (2012: 104) if the population is less than 100 people, then the sample size is taken randomly, but if the population is greater than 100 people, then 10-15% or 20-25% of the population can be taken. Based on this research, because the population is not greater than 100 respondents, the author took 100% of the population in DISKOMINFO, namely 73 respondents. Thus, the use of the entire population without having to draw research as a unit of observation is called a census technique.